2001
DOI: 10.1038/35102599
|View full text |Cite
|
Sign up to set email alerts
|

Gridlock signalling pathway fashions the first embryonic artery

Abstract: Arteries and veins are morphologically, functionally and molecularly very different, but how this distinction is established during vasculogenesis is unknown. Here we show, by lineage tracking in zebrafish embryos, that angioblast precursors for the trunk artery and vein are spatially mixed in the lateral posterior mesoderm. Progeny of each angioblast, however, are restricted to one of the vessels. This arterial-venous decision is guided by gridlock (grl), an artery-restricted gene that is expressed in the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
379
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(402 citation statements)
references
References 30 publications
21
379
0
2
Order By: Relevance
“…22 In this study, we report the analysis of the migration pathway of definitive HSPCs in zebrafish. Using cell labeling technique such as injection of 4,5-dimethoxy-2-nitrobenzyl (DMNB) caged fluorescein (flu) followed by local uncaging, 23,24 we found that flu-labeled cells in the ventral wall of DA at 30 hpf could become rag1-positive T cells, a hematopoietic lineage exclusively generated during definitive hematopoiesis in the thymus, confirming that the cells located in the ventral wall of DA represent the zebrafish counterparts of definitive HSPCs found in the mouse AGM. When the same methodology was applied, we were able to show the migration of definitive HSPCs from the ventral wall of DA to a previously unappreciated hematopoietic organ, the posterior blood island (PBI), located between the caudal artery and caudal vein, prior to populating the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…22 In this study, we report the analysis of the migration pathway of definitive HSPCs in zebrafish. Using cell labeling technique such as injection of 4,5-dimethoxy-2-nitrobenzyl (DMNB) caged fluorescein (flu) followed by local uncaging, 23,24 we found that flu-labeled cells in the ventral wall of DA at 30 hpf could become rag1-positive T cells, a hematopoietic lineage exclusively generated during definitive hematopoiesis in the thymus, confirming that the cells located in the ventral wall of DA represent the zebrafish counterparts of definitive HSPCs found in the mouse AGM. When the same methodology was applied, we were able to show the migration of definitive HSPCs from the ventral wall of DA to a previously unappreciated hematopoietic organ, the posterior blood island (PBI), located between the caudal artery and caudal vein, prior to populating the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Notch also regulates fjx expression in mice and there is clear overlap with notch expression in some, but not all regions of fjx expression (Rock et al, 2005). Notch proteins, together with their ligands, are involved in the specification of the dorsal aorta in zebrafish whilst expression analyses have implicated notch signaling in chick limb arterial development (Vargesson et al, 1998;Lawson et al, 2001;Zhong et al, 2001). This is analogous to the expression of fjx in the developing limb arteries but not the veins.…”
Section: Discussionmentioning
confidence: 99%
“…Toutes sont également exprimées dans le système nerveux où elles contrô-lent la destinée et le guidage des précur-seurs neuronaux et des axones, ce qui suggère leur rôle dans l'établissement du réseau vasculaire. Les CE artérielles du poisson zèbre, du poulet et de la souris expriment sélectivement l'éphrine-B2, la neuropiline 1 (NRP1), le récepteur notch3, le ligand de Notch Delta-like 4 et gridlock [5][6][7][8][9][10][11][9][10][11][12][13][14][15][16]. D'autres molécules sont spécifiquement exprimées par les CE veineuses, notamment EphB4, le récepteur du marqueur artériel éphrine-B2 [12].…”
Section: Les Marqueurs Moléculaires Spécifiques Des Artères Et Des Veunclassified